First-principles calculations of exchange interactions, spin waves, and temperature dependence of magnetization in inverse-Heusler-based spin gapless semiconductors - Jakobsson, A.; P. Mavropoulos; Sasioglu, E.; S. Blügel; Lezaic, M.; Sanyal, B.; Galanakis, I. (PHYSICAL REVIEW B, 2015)
Employing first-principles electronic-structure calculations in conjunction with the frozen-magnon method, we calculate exchange interactions, spin-wave dispersion, and spin-wave stiffness constants in inverse-Heusler-based spin gapless semiconductor (SGS) compounds Mn2CoAl, Ti2MnAl, Cr2ZnSi, Ti2CoSi, and Ti2VAs. We find that their magnetic behavior is similar to the half-metallic ferromagnetic full-Heusler alloys, i.e., the intersublattice exchange interactions play an essential role in the formation of the magnetic ground state and in determining the Curie temperature T-c. All compounds, except Ti2CoSi, possess a ferrimagnetic ground state. Due to the finite energy gap in one spin channel, the exchange interactions decay sharply with the distance, and hence magnetism of these SGSs can be described considering only nearest-and next-nearest-neighbor exchange interactions. The calculated spin-wave dispersion curves are typical for ferrimagnets and ferromagnets. The spin-wave stiffness constants turn out to be larger than those of the elementary 3d ferromagnets. Calculated exchange parameters are used as input to determine the temperature dependence of the magnetization and Tc of the SGSs. We find that the Tc of all compounds is much above the room temperature. The calculated magnetization curve for Mn2CoAl as well as the Curie temperature are in very good agreement with available experimental data. This study is expected to pave the way for a deeper understanding of the magnetic properties of the inverse-Heusler-based SGSs and enhance the interest in these materials for application in spintronic and magnetoelectronic devices.